Analysis of Factors Influencing Individual Taxpayer Compliance with Tax Audits as a Moderating Variable at the North Badung Pratama Tax Office - Kadek Apriada; I Nyoman Kusuma Adnyana Mahaputra; Son of Agung Ayu Sri Pradnya Paramitha (CV Edujavare Publishing, 2026)
Taxes are a crucial source of state revenue for supporting national development financing. Tax revenue optimization is strongly influenced by the level of taxpayer compliance, as reflected in the accuracy of calculating, paying, and reporting tax obligations. However, the level of compliance of individual taxpayers at the North Badung Pratama Tax Office (KPP Pratama) has fluctuated and tended to decline over the past five years. This study aims to analyze the influence of a modern administration system, tax sanctions, tax socialization, and the quality of tax authorities' services on individual taxpayer compliance, as well as to examine the role of tax audits as a moderating variable. The study employed a quantitative approach with a non-probability sampling method through accidental sampling, resulting in 100 respondents registered as individual taxpayers at the North Badung Pratama Tax Office. Data were analyzed using a Moderated Regression Analysis (MRA) test. Data were obtained using a questionnaire in the form of a Google form. The analysis results indicate that a modern administration system, tax sanctions, tax socialization, and the quality of tax authorities' services have a positive effect on taxpayer compliance. Tax audits have been shown to strengthen the influence of a modern administration system, tax sanctions, tax socialization, and the quality of tax authorities' services on compliance. Suggestions for further research can develop this research by adding other variables to increase the level of tax compliance..